PRARANCANGAN PABRIK MONOSODIUM GLUTAMAT DARIMOLASES DENGAN PROSES FERMENTASIKAPASITAS 43.000 TON/TAHUN - Prasojo, Yogi; , Rois Fatoni, S.T. MSc (2017)
ABSTRACT Factory monosodium glutamate from molasses by a fermentation process using bacteria Micrococcus glutamicus with a capacity of 43,000 tons / year is planned to operate for 330 days / year. This product to meet the needs at home and abroad, and as the goal of optimizing the raw materials are abundant molasses. Taking into account the various supporting factors, the plant planned to be built in Central Lampung. Monosodium glutamate produced in the fermenter batches. The reaction takes place at a temperature of 30oC and 1 atm pressure. The reaction takes place in the liquid phase, isothermal reaction irreversible nature, the adiabatic operating conditions at a temperature of 30oC and a pressure of 1 atm. Molasses requirement of 29.331 kg per hour, and produce monosodium glutamate at 5.429,2929 kg per hour. Support utilities include the provision of water extracted from the river, the water needs of 571.726 kg per hour, and the provision of 7.750,434 kg steam per hour obtained from the boiler with fuel by 1.234,32 liters per hour, 618,142 kW of electricity needs were supplied from PLN and used as a backup power generator to the needs of 14,2861 liters of diesel per hour. The factory was set up with the number of employees 162 people. Forms of companies are PT (Company Limited) with a land area of 75.500 m2. Monosodium glutamate factory memerluakan fixed capital of Rp 1.456.311.377.220,00 From an economic analysis of the factory get a pretax profit of Rp 165.931.150.205,00 per year, profit after tax of Rp 124.448.362.654,00 per year. ROI (Return Of Investment) before tax and after tax 11,4%, 8,5%, POT (Pay Out Time) before tax of 4,67 years and 5,39 years after tax. BEP (Break Even Point) amounted to 56,67%, SDP (Shut Down point) amounted to 23,75% and DCF (Discounted Cash Flow) accounted for 18,30%. From the data analysis of the feasibility of this plant concluded lucrative and worth is established. Kata kunci : Monosodium Glutamat,Molases, Micrococcus glutamicus,Fermentor Batch,Irreversible